Alimentação de estudantes concluintes do curso de nutrição de uma universidade federal do Rio Grande do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Students' eating habits change with admission to university. For some students college life includes leaving the parents' home and moving into student residences and producing their own meals or eating food at restaurants. This work aimed to study the eating habits of last year students of Nutrition at federal university of Rio Grande do Sul. The study is characterized as descriptive and were invited to participate all students regularly enrolled in the supervised internship at the year of 2017. The instrument had two parts: the first one with the questionnaire proposed by the Ministry of Health, named "How is your food" and the second with socioeconomic and demographic questions.The questionnaire was crated in Google Sheets and sent online.Only five students answered the questions. The profile was female (100%) and single (80%).The eating habits was classified as regular (80%) and good (20%). Regarding the consumption of the vegetables and milk, 100% of the students did not reach the daily recommendations. The consumption of meat and eggs and fruit was adequate for 40% of students and the legumes was 60%. It has been observed that students, although they include the food groups in the diet, still consume them in inadequate quantities. Therefore, we conclude that the knowledge obtained during the course is not fully incorporated into the students' food routine.
Keywords: Hábitos alimentares; Qualidade de vida; Universitário; Eating habits; Quality of life; College students; CNPQ::CIENCIAS DA SAUDE